Quantitative evaluation of China’s public health emergencies response policies: a PMC index model approach - Yongwen Liu; Min Jiao; Yan Wang; Anning Ma (BMC Public Health)
Abstract Background In recent years, public health emergencies, such as the COVID-19 pandemic and Ebola outbreaks, have occurred with increasing frequency worldwide, posing significant threats to global public health security. Policies serve as the foundation and institutional framework for effective emergency responses. Consequently, evaluating and optimizing the formulation and implementation of Public Health Emergency Response Policies (PHERPs) to enhance emergency response capacities has become an urgent and important research priority. Methods This study developed an evaluation system for PHERPs using content analysis of policy texts, expert consultations, and the PMC-Index model. It quantitatively analyzed 33 central-level PHERPs in China issued between 2003 and 2020. Results The analysis revealed an average PMC-Index score of 6.43 for the 33 PHERPs. The PMC-Surface analysis highlighted that the top three scoring indicators were policy openness, policy structure, and policy area. In contrast, the lowest-scoring indicators were policy timeliness, issuing agency, and incentive measures. Conclusions The study demonstrates was generally good. However, significant variability was observed in the scores of individual indicators across different policies. These findings provide valuable insights into the strengths and weaknesses of PHERPs and offer a reference for optimizing policy design and implementation.